Durabilitas Campuran Porous Asphalt Dengan Limbah Plastik Polietilena Tereftalat (PET) Sebagai Bahan Tambah Pada Aspal - Harahap, Ananda Wirawan Tritama; Putra, Sasana; Herianto, Dwi; Sulistyorini, Rahayu (Jurnal Rekayasa Sipil dan Desain (JRSDD), 2023)
Porous asphalt is an asphalt mixture that has a high pore space, therefore it is necessary to use asphalt modification which is expected to increase the stability of porous asphalt, so that porous asphalt is expected to have better performance. Plastic waste can open up opportunities to be used in the field of highway construction because it is easy to obtain and the price is more economical as a porous asphalt mixture. Referring to this, a research was carried out on the durability of porous asphalt mixtures with polyethylene terephthalate (PET) plastic waste as an additive to asphalt. The purpose of this study was to determine the effect of using PET plastic waste on the durability of porous asphalt mixtures. The method used is a laboratory scale experimental method based on 3 types of testing, namely marshall, cantabro loss and asphalt flow down. The gradation in this study used the Australian Asphalt Pavement Association (AAPA) 2004 open graded. The test results showed successively the immersion effect of porous asphalt with the addition of 0%, 5% and 7.5% PET plastic resulted in a decrease in the IDP value (Index Durability First) of 1.25%, 0.89% and 0.83% , and also a decrease in the value of IDK (Second Durability Index) based on the value of loss of strength of 44.12%, 33.31% and 30.52%. This shows that porous asphalt mixed with PET plastic has better durability than without PET.